2021
DOI: 10.1080/14786419.2020.1865954
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and pharmacological evaluation of novel Artemisinin-Thymol

Abstract: A molecular hybridization of natural products is a new concept in drug discovery and having critical roles to design new molecules with improved biological properties. Hybrid molecules display higher biological activities when compared to the parent drugs. Moreover, they create new biological properties. In the present study, two natural products (thymol and artemisinin (ART)) are used for the synthesis of new hybrid thymol-artemisinin molecule. After characterization, the cytotoxic activity of ART-thymol is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Nevertheless, it can block the binding of SARS-CoV-2 to ACE2 in vitro (Wang et al 2020). On similar basis, other antimalarial agents such as artemisinins demonstrated in vitro inhibition of SARS-CoV-2 (Krishna et al 2021;Kavak et al 2021). Extracts from the sweet woodworm Artemisia annua have been used for centuries in Chinese traditional medicine for treating the symptoms of febrile diseases, tidal fever and summer heat stroke (Brown 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it can block the binding of SARS-CoV-2 to ACE2 in vitro (Wang et al 2020). On similar basis, other antimalarial agents such as artemisinins demonstrated in vitro inhibition of SARS-CoV-2 (Krishna et al 2021;Kavak et al 2021). Extracts from the sweet woodworm Artemisia annua have been used for centuries in Chinese traditional medicine for treating the symptoms of febrile diseases, tidal fever and summer heat stroke (Brown 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To splice thymol and artemisinin to synthesize a new artemisinin thymol conjugate and tested the cytotoxic activity of the compound on different cancer cell lines in vitro (Figure 2). The results showed that the new compound had inhibitory effects on HepG2 cells, LNCaP cells, Caco‐2 cells, HeLa cells, and HEK293 cells, especially on human colorectal adenocarcinoma Caco‐2 22 . Dihydroartemisinin (DHA) is obtained by reducing artemisinin with sodium borohydride.…”
Section: Structural Integration Based On the Active Components And Mo...mentioning
confidence: 99%
“…The relative gene expression levels were normalized to glyceraldehyde 3-phosphate dehydrogenase (GAPDH). For the determination of mRNA levels, the 2 −ΔΔCt method was used as described previously [26]. Primer sequences for all genes were acquired from the NCBI database (Supplementary Table S1) and were synthesized by Sentebiolab (Sentegen, Turkey).…”
Section: Rna Isolation and Quantitative Real-time Pcr (Rt-qpcr)mentioning
confidence: 99%